EXPERIENCE OF PROLONGED VALPROATE USE IN ADULT PATIENTS WITH FOCAL FORMS OF EPILEPSY (RESULTS OF OBSERVATION HELD IN OUT-PATIENT CLINICS OF MOSCOW) - S. G. Burd; A. V. Lebedeva; I. Yu. Artyomova; O. L. Badalyan; M. A. Bogomazova; I. I. Zhuravlyeva; A. M. Ismailov; E. G. Komelkova; L. N. Lesinker; Yu. I. Logvinov; O. V. Otcheskaya; S. V. Petrov; et al. (Эпилепсия и пароксизмальные состояния, 2016)
Results of Depakine Chronosphere use in Moscow city out-patient clinics are demonstrated in the article. 48 patients with focal forms of epilepsy (cryptogenic and symptomatic) were examined: 32 men and 16 women in age of 16 - 59 years with different duration of disease and different types of seizures. Depakine Chronosphere was indicated to patients who were already taking antiepileptic drugs in monotherapy with efficacy of 50% and more, and also to patients with drug remission, but with side effects, requiring changes of current indications. Results of the observation demonstrated high efficacy of Depakine Chronosphere in adult patients with different forms of focal epilepsy in monotherapy and also its use possibility in case of noneffective or poor tolerability of other valproates and carbamazepine.